THE ROLE OF ARTIFICIAL INTELLIGENCE IN INFLUENCEING ORGANIZATIONAL CULTURE - HASAN, ISAL ANWAR (Gema Kampus IISIP YAPIS Biak, 2026)
Artificial Intelligence (AI), one of the most transformative technologies, has brought significant changes. The rapid advancement of Artificial Intelligence (AI) technology is fundamentally changing the way organizations operate, communicate, and make decisions. Artificial Intelligence (AI) has become an integral part of organizational strategy. The aim of this research is to examine the role of Artificial Intelligence in influencing organizational culture. The method used in this study is a Systematic Literature Review (SLR), which identifies, evaluates, and synthesizes the results of previous research using transparent, structured, and replicable procedures. The research findings show that AI influences organizational culture through four main mechanisms, namely: 1. Transformation of Decision-Making Processes and Power Structures. 2. Evolution of Communication Patterns and Collaboration Methods. 3. Redefinition of Work Values, Professional Identity, and Organizational Learning. 4. Artificial Intelligence (AI) Ethics and Transformation of Organizational Governance